Thermochemical-Mechanical Assessment of Washed and Torrefied Biomass Co-Firing in Boilers for a Sustainable Energy Transition - Hadi Prayitno; Heri Rustamaji; Yasir Arafat; Amrul; Angga Darma Prabowo (The Journal of Indonesia Sustainable Development Planning, 2026)
Despite extensive research on biomass co-firing, gaps remain regarding the combined effects of washing, torrefaction, and analytical indices on emission reduction, slagging, and fouling for heterogeneous Indonesian biomass. This study demonstrates that pre-treatment enhances energy density, improves HHV, and imparts coal-like combustion characteristics, reducing CO₂ by up to 12% and SO₂ by up to 30%, while NOₓ remains fuel-dependent. Washing lowers alkali metals, mitigating slagging and fouling, and torrefaction stabilizes biomass thermally, improving operational reliability. Findings highlight the CO₂-NOₓ trade-off, guiding biomass blend selection and combustion management. This research provides actionable insights for policymakers and energy stakeholders, supporting Indonesia’s renewable energy transition, SDGs, and a scalable pathway toward carbon neutrality by 2060.